The incidence of meniscal cyst formation following meniscal repair using the all‐inside suture anchor device is comparable to conventional techniques - Kazumi Goto; Takaki Sanada; Eisaburo Honda; Shin Sameshima; Miyu Inagawa; Yutaro Ishida; Koji Matsuo; Ryota Kuzuhara; Hiroshi Iwaso (Journal of Experimental Orthopaedics, 2024)
Abstract Purpose Post‐operative meniscal cyst formation occurs following all‐inside device meniscal repair. This study aimed to compare the incidence of cysts in patients who underwent meniscal repair with and without all‐inside suture devices. Methods This retrospective study included 227 knees that underwent meniscal repair between 2021 and 2022. The incidence of post‐operative meniscal cysts was compared between patients who underwent repair using an all‐inside suture anchor device (Group SA) and those who did not use an anchor (Group NA), based on post‐operative magnetic resonance imaging (MRI) findings. Risk factors, such as the number of anchors used, were investigated. Using a subgroup analysis, the incidence of meniscal cysts based on the type of device used was investigated. Results Groups SA and NA comprised 125 and 102 knees, respectively. Group SA had 11 cases of cysts (9% incidence), whereas Group NA had 7 cases (7% incidence), and no statistically significant difference was observed (p = 0.63). Symptomatic cysts were observed in two patients (1.6%) in Group SA, whereas none was observed in Group NA (0%); the difference was not significant (p = 0.50). Factors such as the number of anchors and sutures used and MRI timing were not identified as risk factors. Cyst incidence varied according to anchor type: Stryker AIR+ (4 out of 55, 7%), Smith & Nephew Fast‐Fix 360 (7 out of 56, 13%) and Arthrex Fiber Stitch (0 out of 26, 0%), with no significant difference found (p = 0.14). Conclusion The incidence of cysts in patients undergoing meniscal repair with an all‐inside suture anchor device was 9%, showing no significant difference compared with Group NA. Cyst incidence was not affected by device type. Level of Evidence Level III, retrospective comparative study.